(untitled) (International Journal of Current Engineering and Technology, 2015)
Wireless sensor networks are basically energy constraint network. Carrying the limited energy for longer time is the challenge in hierarchical clustering algorithms. Clustering in WSN provides efficient way of utilizing energy to increase the network lifetime. Applications of WSN are surveillance networks, military applications, disaster recovery etc. In WSN, all nodes participate in cluster head selection which may give rise to death of border nodes very soon as border nodes participate in cluster head selection and sensing the environment for data. To avoid this situation we proposed a method which divides the network into inner area nodes and border area nodes allowing only the inner area nodes to participate in the cluster head selection. Hence this method not only increases the life time of border nodes but also the entire network life time. The cluster heads are selected within the inner nodes, based on dynamic cluster head selection scheme. The proposed scheme uses the residual energy of each node to elect as cluster head, if it finds multiple nodes with same residual energy then it considers cost values of those nodes to decide which node is made as cluster head.